The Scoping Examination of How Gender Preference Affects Girls’ Access to Quality Education in both Developed and Developing Nations (OCEM Journal of Management, Technology & Social Sciences, 2026)
In the discourse of gender studies, parental gender preference leading to childhood discrimination remains a significant and contentious global issue. This study addresses the pervasive problem where parents allocate a disproportionately larger share of household resources to their sons’ education compared to their daughters’. This allocation bias is often rooted in traditional beliefs that daughters are transient family members expected to marry and leave. At the same time, sons are the primary caregivers for parents in old age. The core objective of this study is to systematically identify, review, and evaluate the existing body of research on parental gender preferences in the allocation of household resources for children’s education globally.Using a rigorous scoping review methodology, our research aimed to map the extent and nature of the literature, clarify research objectives, and reduce misconceptions about discriminatory discourse in early childhood education across both developed and developing nations. The scoping review highlighted that millions of girls under the age of 18 are still denied access to a high-quality education due to above-mentioned pervasive gender biases.The collected evidence revealed that while the form of discrimination can differentiate geographically, the underlying preference for sons in educational investment is a consistent global phenomenon. The findings strongly advocate for urgent policy interventions and community-level awareness campaigns to challenge above-mentioned entrenched norms and ensure equitable access to quality education for all children, regardless of gender.